POLA PENGEMBANGAN AGROINDUSTRI BERBASIS PERIKANAN LAUT DI KECAMATAN PUGER KABUPATEN JEMBER - Djoko Soejono (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2008)
The aim of this research were (1) to understand the efficiency of production cost, income farmer and added value, (2) to find agroindustry developing pattern on sea fisheries in Puger Subdistrict, Jember Regency. Descriptive and analytical method used to find the objective. Than, the sample taken by disproportionate stratified random sampling by stratifying the business pattern that actually in terasi product, flour and fish fried and medium drying  fish, boiled fish and flour fish. The result shows that the sea fisheries is efficient due to R/C ratio > 1. its attend profit for farmer. So, Production cost efficiency is influenced by income total and total cost. Furthermore, income farmer is influenced by harvested product and product price per kg. The added value from agro industry is positive and different one another. Its influenced by product price, raw material, and market structure. Developing agro industry on sea fisheries could be released by incubator program. The program focus on managing, presenting the topic, and advisor the client, that tied on (1) increasing product quality and make the standardization, (2) spreading the  information and market  (3) financial managing and (4) making organization. Key words: sea fishery agroindustry, efficiency and added value.